2022
DOI: 10.1111/ane.13701
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and alternative medicine for treating epilepsy in China: A systematic review

Abstract: There are about 10 million people with epilepsy (PWE) in China. In addition to therapies approved by the National Medical Products Administration, the use of complementary and alternative medicine (CAM) is prevalent in Chines PWE. These CAM therapies mainly comprise traditional Chinese medicine herbs (TCMHs), acupuncture, and music. A retrospective literature search was performed to summarize the updates of CAM in China in the past ten years, and sixty‐two papers were finally included. In this following review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…The robustness of the results of this study is further supported by TSA findings. This aligns with the results of previous studies that reported favorable outcomes from the combined use of herbal medicine and acupuncture for epilepsy in both children and adults [ 19 , 39 41 ]. Notably, an updated meta-analysis demonstrated the use of herbal medicine as a promising clinical strategy for epilepsy across age groups [ 19 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The robustness of the results of this study is further supported by TSA findings. This aligns with the results of previous studies that reported favorable outcomes from the combined use of herbal medicine and acupuncture for epilepsy in both children and adults [ 19 , 39 41 ]. Notably, an updated meta-analysis demonstrated the use of herbal medicine as a promising clinical strategy for epilepsy across age groups [ 19 ].…”
Section: Discussionsupporting
confidence: 91%
“…Another comprehensive review of 17 RCTs that included participants aged between 1 and 66 years highlighted the potential of herbal medicine to improve seizure control and normalize EEG patterns [ 38 ]. Furthermore, a specific review delved into the molecular mechanisms of herbal medicine in pediatric epilepsy treatment, demonstrating its multifaceted approach in regulating neurotransmitters, ion channels, inflammation, apoptosis-related genes, and oxidative stress [ 39 ]. Despite this array of evidence, a gap exists in research specifically focused on pediatric patients with unique pharmacokinetic and pharmacodynamic profiles compared with adults [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were no systematic reviews and meta-analyses that addressed the treatment effectiveness of acupuncture combined with Western medicine in patients with epilepsy. At present, acupuncture for epilepsy is widely used in clinical practice, and most of them report reliable efficacy, indicating that acupuncture for epilepsy has certain advantages and development potential ( Zhong, 2014 ; Zhao et al, 2022 ). Throughout the papers published in recent years on the treatment of epilepsy with acupuncture, it can be found that a variety of acupuncture therapies, including acupoint embedding and electroacupuncture, have obvious effects, and have the advantages of simple operation, economic and inexpensive and long duration of therapeutic effects, which have obvious advantages in the treatment of epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the use of complementary and alternative medicine (CAM) is prevalent in Chinese patients with epilepsy. In the review “Complementary and Alternative Medicine for treating epilepsy in China: A systematic review,” Zhao et al focused on three main CAM therapies including traditional Chinese medicine herbs (TCMHs), acupuncture, and music 10 . For the neuromodulation, Xue et al emphasized on three approved neuromodulation therapies: vagus nerve stimulation (VNS), deep brain stimulation of the anterior nucleus of the thalamus (ANT‐DBS), and closed‐loop responsive neurostimulation (RNS) in their review “Neuromodulation in drug‐resistant epilepsy: a review of current knowledge.” 11 Yan et al described the clinical evidence on the possible mechanism, anti‐epileptic effect, and safety of deep brain stimulation of the subthalamic nucleus (STN‐DBS) in their review “Deep brain stimulation of the subthalamic nucleus for epilepsy.” 12 For the management of neurologic critically ill patients, in the review “Non‐convulsive seizures and non‐convulsive status epilepticus in neuro‐intensive care unit,” Wang et al summarize the EEG, clinical, epidemiological, diagnostic, and therapeutic knowledge of NCS and NCSE in the neuro‐intensive care setting 13 …”
mentioning
confidence: 99%